René : dokumentární film - Třeštíková, Helena (2008)
This is a film which tells a powerful story filmed over 20 years about an extraordinary character on the edge of society. Known for shooting her subjects for long periods of time, Helena Třeštíková began shooting her subject in 1989 at a youth correctional facility in Libkovice. René has been in prison since he was 16. With raw authenticity, the director records the luckless fate of René over a period of twenty years as he yo-yos between prison and freedom. The life of René, who successfully styles himself in the role of a desperado, unfolds against a backdrop of important political events occurring in the Czech Republic and beyond its borders. The Velvet Revolution, the presidential election, 9/11 and the Czech Republic's accession to the EU, all this is digested by René, mostly from the confines of various prisons. The documentary includes René's letters to the director